Teacher’s Knowledge about Sociolinguistics in EFL Pedagogy. A Study From Classroom Implementation of Curriculum 2013 - Edi Ramawijaya Putra (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2019)
this research article discusses EFL teachers’ knowledge about sociolinguistics in EFL pedagogy that applied in the classical context of English subjects under Curriculum 2013 implementation. One targeted-sample of EFL classroom was observed to explore the focus. Using a qualitative approach, this study had found unique understandings from the participant that deals with their metacognition of sociolinguistics in EFL pedagogy. The knowledge was clustered into Bloom’s taxonomy of knowledge which was considered to be the essential cognition that must be understood by EFL teachers in Indonesia. These knowledge include factual, conceptual, and procedural dimensions. The results of this study provide several pedagogical implications such as revitalizing the orientation of sociolinguistic to attain learning objectives stated in the curriculum, making sense the objectives of English in Curriculum 2013, and re-orienting EFL teachers’ professional development as well as pre-service teachers’ education to engage more on the development of the practices in EFL classroom through the benefits of the knowledge of sociolinguistics in EFL pedagogy.